2017
DOI: 10.1177/1748006x17742778
|View full text |Cite
|
Sign up to set email alerts
|

Cost-oriented component redundancy allocation for a communication system subject to correlated failures and a transmission reliability threshold

Abstract: Transmission quality of a communication/computer system is a high-level objective of system supervisors. Therefore, transmission reliability improvement or optimization is an important issue for many organizations. One way to maximize transmission reliability is to model the system as a stochastic communication network including arcs and nodes and then determine the optimal component redundancy allocation. However, modern components are highly reliable. Thus, a decision maker may be more concerned about cost t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Yi et al 7 set up the model to minimize the system cost of power-shift steering transmission and showed the efficiency of the model. Yeh et al 8 allocated the component reliability for minimizing allocation cost and demonstrated the model through several benchmark networks. These studies mainly adopted research and development (R & D) expense as allocation objective of the model, which may cause the allocated subsystem reliability conservatively and can barely meet the product demand.…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al 7 set up the model to minimize the system cost of power-shift steering transmission and showed the efficiency of the model. Yeh et al 8 allocated the component reliability for minimizing allocation cost and demonstrated the model through several benchmark networks. These studies mainly adopted research and development (R & D) expense as allocation objective of the model, which may cause the allocated subsystem reliability conservatively and can barely meet the product demand.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], the system reliability-redundancy allocation with a cold standby strategy is considered, and an enhanced ENCOA optimization algorithm is proposed. In [6], the polynomial cost function of reliability allocation is discussed, and the geometric programming method is found in the cost function and reliability constraint, considering all its properties of multivariate monotonicity and convexity. A reliability allocation model based on expert knowledge and gray system theory is proposed in [7].…”
Section: Introductionmentioning
confidence: 99%